(untitled) (Editora Impacto Científico, 2025)
Skin cancer is a neoplasm that arises from the abnormal growth of mutated cells, mostly triggered by excessive exposure to UV radiation. Its incidence is more frequent in regions that are more exposed to radiation, such as the face, ear pinna and neck. Due to its high incidence and risk potential, skin cancer is one of the most important health problems today. Non-melanoma skin cancer is the most common cancer in Brazil and accounts for around 30% of all malignant tumors registered in the country. It has a high cure rate if detected and treated early. Despite its low incidence, melanoma skin cancer has a worse prognosis and high metastatic potential. There are several diagnostic methods for skin cancer, such as clinical history, clinical examination of the skin, dermoscopy, biopsy, the latter being mandatory for anatomopathological confirmation. The treatment of choice should offer the best balance between cure and aesthetic and functional results. Surgery is the first-line treatment for melanomas and non-melanomas. The procedure removes the entire tumor with free margins. Faced with the magnitude of the global public health problem of skin cancer, nurses have a wide field of action in terms of prevention, early detection, active participation in the treatment process and helping to control the disease. In the field of prevention, given the nurse’s nature as an educator, he or she can act by advising on fundamental chemical or physical protection measures to minimize the damage caused by exposure to UV radiation and other chemical products that can lead to the development of the disease. During treatment, nurses focus on perioperative nursing care, advising patients and their families on preoperative, postoperative and discharge care, as well as the care and monitoring of adverse effects resulting from clinical treatment.